Scrapping Menstrual Blood Stains According to South Sulawesi Ulama and Intellectual from Perspective of Ma‘āni-Ḥadīth - Ali, Muhammad; Risdahyanti, Risdahyanti; Khaerah, Silfi; Asmullah, Asmullah; Fatmal, Abd. Bashir (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Scrapping menstrual blood stains is prescribed as a way to purify clothing contaminated by menstrual blood. This research explores the rulings on scraping menstrual blood stains from the perspectives of female ulama and intellectual in South Sulawesi, viewed through the lens of maʻānī al-hadīth. This study employs a qualitative library research approach, utilizing maʻānī al-hadīth. Data is gathered from hadith collections that discuss the practice of scraping menstrual blood stains. Interviews were conducted to gain additional perspectives from ulama and intellectuals in South Sulawesi. The results indicate that a contextual analysis of hadith reveals an injunction to purify clothing affected by menstrual blood, specifically by scraping off the residue adhering to the fabric. According to the ulama and intellectuals of South Sulawesi, a contextual understanding of hadith related to scraping menstrual blood stains permits the use of cleaning agents, such as detergents, to maximize efforts to clean stains or menstrual blood that adheres to the fabric. Furthermore, if the stain is irremovable, the fabric or clothing may be used for prayer, demonstrating a leniency in religious practice. In the context of maʻānī al-ḥadīth, a textual understanding can create a rigid legal character, potentially diminishing the universal message of the hadith, while a contextual approach can reveal substantive values that remain relevant in modern society.